ANKOS 4th Staff Exchange Program Experience: Izmir's Beautiful Libraries - Aka, Neslihan (Turkish Librarians Assoc, 2016)
In this article, ANKOS Staff Exchange Program, one of Anatolian University Libraries Consortium (ANKOS)'s services and first starting in 2012, is explained. Impressions about ANKOS 4th Staff Exchange Program in Izmir are shared.
Keywords: Anatolian University Libraries Consortium; ANKOS; staff exchange program; professional development; knowledge and experience sharing